Pengaruh Kecerdasan Emosional, Servant Leadership, dan Komitmen Organisasi terhadap Organizational Citizenship Behavior di PT.ABC - Sellya Alma; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
The purpose of this study is to establish the relationship between PT.ABC's organizational citizenship behavior and intelligence, servant leadership, and organizational commitment. This is a quantitative study conducted with the use of SPSS Statistics. A total of eighty PT.ABC employees were selected using the approach of purposive sampling. This study's measurement scale is a Likert scale. The measuring instrument is a paper-based and Google Forms-based survey. According to the findings of this study, emotional intelligence has a positive influence on organizational citizenship behavior, servant leadership has a positive influence on organizational citizenship behavior, organizational commitment has a positive influence on organizational citizenship behavior, and emotional intelligence, servant leadership, and organizational commitment all have a positive influence on organizational citizenship behavior simultaneously. The benefits of PT ABC's research will enhance organizational citizenship through emotional intelligence, servant leadership, and organizational commitment.